The effect of sexual health education on sexual activity, sexual quality of life, and sexual violence in pregnancy: a prospective randomized controlled trial - Shiva Alizadeh; Hedyeh Riazi; Hamid Alavi Majd; Giti Ozgoli (BMC, 2021)
Abstract Background Some women avoid sexual intercourse during pregnancy due to the physiological changes they undergo during this period as well as their fear of causing harm to the fetus and to themselves, which can lead to problems in sexual health. The aim of the present study was to investigate the effects of a sexual health education package on the dimensions of sexual health in pregnant women. Methods This randomized, longitudinal, clinical trial was carried out in 2018-2019 on 154 pregnant women in early to late pregnancy who presented to comprehensive health centers in Rasht, Iran, and were divided into three groups: Group A or the training group (50 participants), Group B or the self-training group (53 participants), and Group C or the control group (51 participants). The study tools included the Pregnancy Sexual Response Inventory (PSRI), the Sexual Quality of Life-Female (SQOL-F) and the Sexual Violence Questionnaire. The dimensions of sexual health were examined before beginning each intervention in each trimester of pregnancy and then at the end of pregnancy using these questionnaires. The collected data were analyzed using statistical tests, namely the Chi-square test, one-way ANOVA, Cochrane's test, and the repeated measures ANOVA at a significance level of P < 0.05. Results There was no statistically significant difference in the mean total scores of SQOL-F and PSRI in the three groups at baseline. As for the intergroup results, there was a statistically significant difference in the mean score of SQOL-F and PSRI at the end of pregnancy. The mean scores of PSRI and SQOL-F in the training group (Group A) increased from the beginning to the end of pregnancy compared to the control and self-training groups. As for the intergroup comparisons, there was no statistically significant difference in the mean total scores of sexual violence among the pregnant women in the different groups in the third trimester of pregnancy and at the end of the third trimester. Although sexual violence was not statistically significant, the number of sexually-violated women in the training group decreased during the training period compared to the self-training and control groups. Conclusion The results obtained in the intervention group compared to the control group revealed the effectiveness of the sexual health education package in terms of improvement in the dimensions of sexual health. According to the results, in order to maintain and promote the sexual health of pregnant women, health care providers are recommended to offer sexual health training during pregnancy along with other health care services. Trial registration IRCT20190427043398N1 ; the trial was registered on June 2, 2019. (retrospective registration).